First-Principles Calculations of the Structure Stability and Mechanical Properties of LiFeAs and NaFeAs under Pressure - Zhengquan Hu; Weiwei Xu; Cai Chen; Yufeng Wen; Lili Liu (Advances in Materials Science and Engineering)
The lattice parameters and elastic constants of the tetragonal LiFeAs and NaFeAs under different pressures have been investigated by using the first-principles calculations. It is found that their lattice parameters at 0 GPa are in agreement with the available experimental data. By the elastic stability criteria under isotropic pressure, it is found that LiFeAs and NaFeAs with the tetragonal structure are not mechanically stable above 16 GPa and 18 GPa, respectively. Besides, Pugh’s modulus ratio, Poisson’s ratio, Vickers hardness, and elastic anisotropy factors of LiFeAs in the pressure range of 0–16 GPa and NaFeAs in the pressure range of 0–18 GPa are systematically investigated. It is shown that their ductilities increase with increasing pressure, and the ductility of NaFeAs is superior to that of LiFeAs under different pressures.